Hari tanpa Daging: Studi Pasca Kolonial tentang Identitas, Migrasi, dan Kenangan yang Tumpang Tindih - Shahzaib Hassan (Neolectura, 2022)
This research paper aims to critically analyze the political, lingual and religious identity crises of the people of the third world. For that purpose, the primary text selected is Meatless Days written by Sara Suleri. The theoretical framework employed to provide character analysis is post-colonialism of Edward Said and Gayatri Spivak. Throughout this research, the concept of “the orient